Distinct interferon‐gamma and interleukin‐9 expression in cutaneous and oral lichen planus. (21st October 2016) - Weber, B.; Schlapbach, C.; Stuck, M.; Simon, H.‐U.; Borradori, L.; Beltraminelli, H.; Simon, D.
Abstract: Background: Cutaneous (CLP) and oral lichen planus (OLP) as the main subtypes of lichen planus (LP) present with different clinical manifestation and disease course, although their histopathologic features such as the band‐like lymphocyte infiltrate and keratinocyte apoptosis are similar. So far, the underlying cellular and molecular mechanisms remain poorly understood. Objective: The aim of this study was to characterize and compare the in situ cellular infiltrates, cytokine expression profiles and apoptosis markers in CLP and OLP. Methods: Using immunofluorescence staining and laser scanning microscopy, we evaluated the cellular infiltrate (CD1a, CD3, CD4, CD8, CD21, CD57, CD123), cytokine expression (interleukin (IL)‐1, IL‐6, IL‐9, IL‐10, IL‐17, IL‐22, IL‐23, tumour necrosis factor‐α, transforming growth factor‐β, interferon (IFN)‐γ), and apoptosis markers (Fas, Fas ligand, cleaved caspase‐3, TUNEL) of 21 anonymized biopsy specimens of LP (11 CLP, 10 OLP). Results: Among infiltrating cells mainly T cells and natural killer (NK) cells as well as plasmacytoid dendritic cells (DC) were observed. A predominance of CD8+ T cells was noted in OLP. In both CLP and OLP, T helper (Th)1, Th9, Th17, and Th22‐type cytokines were expressed. The expression of IL‐9, IFN‐γ and IL‐22 was higher in CLP compared to that of OLP ( P = 0.0165; P = 0.0016; P = 0.052 respectively). Expression of Fas and Fas ligand as well as cleaved caspase‐3‐positive cells was observed in the epithelium of all LP samples. Conclusions: The cell and cytokine patterns of CLP and OLP were partially distinct and generally resembled those reported for autoimmune diseases. The presence of CD8+ and NK cells as well as Fas/Fas ligand expression suggested that various pathways involved in keratinocyte apoptosis are relevant for LP. These results might help to establish targeted therapies for LP.